TRAP1: a viable therapeutic target for future cancer treatments?. (3rd August 2017) - Lettini, Giacomo; Maddalena, Francesca; Sisinni, Lorenza; Condelli, Valentina; Matassa, Danilo Swann; Costi, Maria Paola; Simoni, Daniele; Esposito, Franca; Landriscina, Matteo
ABSTRACT: Introduction : HSP90 molecular chaperones (i.e., HSP90α, HSP90β, GRP94 and TRAP1) are potential therapeutic targets to design novel anticancer agents. However, despite numerous designed HSP90 inhibitors, most of them have failed due to unfavorable toxicity profiles and lack of specificity toward different HSP90 paralogs. Indeed, a major limitation in this field is the high structural homology between different HSP90 chaperones, which significantly limits our capacity to design paralog-specific inhibitors. Area covered : This review examines the relevance of TRAP1 in tumor development and progression, with an emphasis on its oncogenic/oncosuppressive role in specific human malignancies and its multifaceted and context-dependent functions in cancer cells. Herein, we discuss the rationale for considering TRAP1 as a potential molecular target and the strategies used to date, to achieve its compartmentalized inhibition directly in mitochondria. Expert opinion : TRAP1 targeting may represent a promising strategy for cancer therapy, based on the increasing and compelling evidence supporting TRAP1 involvement in human carcinogenesis. However, considering the complexity of TRAP1 biology, future strategies of drug discovery need to improve selectivity and specificity toward TRAP1 respect to other HSP90 paralogs. The characterization of specific human malignancies suitable for TRAP1 targeting is also mandatory.